EFFICACY AND COMPLICATIONS OF IMMUNOSUPPRESSIVE THERAPY IN UTERINE TRANSPLANTATION - Yuldasheva Barnokhonim; Rakhmatullayeva Aziza Farxodovna (Web of Journals Publishing, 2025)
Uterine transplantation represents a novel milestone in reproductive medicine, offering hope for women deprived of the ability to become mothers. Postoperatively, immunosuppressive therapy is administered to prevent graft rejection. This article analyzes the efficacy of immunosuppressive drugs, their impact on pregnancy outcomes following uterine transplantation, and potential complications. Long-term results and future perspectives of this therapy are also discussed.
Keywords: Uterine transplantation, immunosuppressive therapy, complications, reproductive medicine.